An Analysis of Indonesian Gen-Z in Using E-wallet and Its Impact on Impulsive Buying - Sherin A. Chandra; Tri Wismiarsi; Sentot Basuki Prayitno (Journal on Education, 2024)
E-commerce has grown significantly in recent years, due to technological developments and a shifting consumer landscape. Along with this expansion, the introduction of digital methods of payment, such as e-wallets, has transformed the way online purchases are handled. E-wallets have given customers convenience, security, and more financial flexibility, resulting in an adjustment in consumer purchasing behavior within the e-commerce ecosystem. This study investigates the impact of an e-wallet (ShopeePay) adoption on impulse buying behavior in e-commerce (Shopee), specifically on Gen-Z users. This paper also examines if customers' satisfaction with utilizing e-wallets substantially impacts their impulsive purchasing behavior. PLS-SEM was performed using 280 valid responses from active ShopeePay Gen-Z consumers gathered via an online survey. The results revealed that perceived interactivity and subjective norm positively affected satisfaction with using an e-wallet, yet perceived risk had no significant effect on satisfaction with an e-wallet. Moreover, perceived interactivity, perceived risk, and subjective norms are found to significantly influence impulse buying, with satisfaction as the mediating variable.